Concurrent MAC with short signaling for multi-hop wireless mesh networks - Gannapathy, Vigneswara Rao; Ahmad, Mohd Riduan; Suaidi, Mohamad Kadim; Johal, Muhammad Syahrir; Dutkiewicz, Eryk (2009)
The IEEE 802.11 distributed coordination function (DCF) medium access control (MAC) protocol continues to suffer from throughput degradation when directly applied in multi-hop wireless mesh network (WMN). The request-to-send/clear-to-send (RTS/CTS) signaling partially solved hidden node problems however the exposed node problems remain unaddressed. The IEEE 802.11 MAC does not allow the exposed nodes to initiates its transmission for the entire duration of ongoing transmission over multi-hop network leads to throughput degradation. Moreover, the amount of needed signaling packets takes place at every hop reduces the overall multi-hop throughput significantly. This project proposes a set of enhancement to the existing IEEE 802.11 DCF MAC by enabling concurrent transmission by the exposed nodes and reduces the amount of signaling packets (CMAC-SS) required at every hop until the data packet reaches its destination. Analytical models are developed and simulated over quasi-static Rayleigh fading channel. The multi-hop network performances are evaluated in terms of throughput and delay. The CMAC-SS protocol outperforms the existing IEEE DCF MAC with more than 14% increase in overall throughput of multi-hop WMN.